(untitled) (Al-Aasar, 2025)
Water serves as the fundamental element of life, sustaining ecosystems, biodiversity, and human civilization on Earth. The Holy Qur’an emphasizes its profound significance, repeatedly urging humanity to reflect on water’s various forms and states as evident signs of Allah’s supreme creativity, artistry, and compassionate lordship (Rububiyyah). Uniquely among substances, water exists naturally in all three physical states—solid, liquid, and gas—and covers about 71% of the Earth’s surface, providing essential habitats through oceans, seas, rivers, streams, and underground reservoirs for countless species. The perpetual hydrologic cycle, involving evaporation, cloud formation, rainfall, infiltration, and replenishment of aquifers and surface waters, ensures the continuous fulfillment of humanity’s nutritional, hygienic, industrial, agricultural, environmental, and navigational requirements. The Qur’an describes this marvelous water cycle in numerous verses across different contexts, portraying it as a perpetual blessing and a testament to the flawless design of the Great Creator. It highlights that water predates the creation of the heavens and earth, with Allah’s Throne established upon it (Qur’an 11:7). Every form of life—animal and plant—depends on water for growth and sustenance. The Qur’an mentions water-related phenomena with remarkable frequency: rain (63 times), rivers (54 times), seas (41 times), springs (20 times), and underground streams (multiple references in paradise and worldly contexts), underscoring their relative importance. This divine exposition invites reflection on water’s role in sustaining life and calls for gratitude toward the Merciful Provider who maintains this intricate, balanced system.